Cashew Nut Shell Derived Porous Activated Carbon Electrodes for "Water‐in‐Salt" Electrolyte Based Symmetric Supercapacitor. Issue 23 (14th June 2022) - Pulikkottil, Merin; Antony, Henock; Muralidharan, Malamal Neelanchery; Gopalan, Elavumkal Veena; Ansari, Seema
Abstract: Biomass derived activated carbon has attracted well‐deserved attention in the realm of energy storage applications due to its high porosity and excellent electrochemical properties. In this study, cashew nutshell derived activated carbon (CNSAC) exhibits a highly interconnected and honeycomb like microporous structure with a large specific surface area of 835 m 2 g −1 and a high pore volume of 0.4 m 3 g −1 . These superior structural features of CNSAC facilitate rapid diffusion of electrolyte and improve its electrochemical efficiency, which is desirable for electrode material. Fabrication of symmetrical supercapacitors (SSC) employing water in salt (WIS) electrolyte validates the outstanding electrochemical performance of CNSAC electrode material. WIS based SSC had a remarkable specific capacitance of 110 Fg −1 at a current density of 1 Ag −1 over a wider electrochemical stability window of 0–2 V, suggesting that WIS electrolytes can address the limitations of conventional aqueous electrolytes and have significant potential for diverse supercapacitor applications. Abstract : Cashew nut shell derived activated carbon (CNSAC) possesses remarkable structural and electrochemical properties, making it ideal for practical electrode applications. The specific capacitance of symmetrical supercapacitors (SSC) fabricated using CNSAC‐based electrode material and water in a salt (WIS) electrolyte is higher than that of SSC with typical aqueous electrolytes. WIS electrolytes also exhibit a wider electrochemical stability window. This study suggests that WIS electrolytes can overcome the constraints of conventional aqueous electrolytes and have significant potential in supercapacitor applications.